HA PERAN MODAL SOSIAL DALAM PENGAMBILAN KEPUTUSAN PRODUKSI DAN RELASI PRODUKSI PEMBUDIDAYA RUMPUT LAUT DI DESA PUNAGA KABUPATEN TAKALAR - Agusanty, Harnita; Tahir, Ratnawati; Khaeriyah, Andi; Anwar, Asni; Arief, Andi Adri; Pallampa, Andi Azka Yuriant (Hasanuddin University, 2025)
This study aims to analyze the role of social capital in production decision-making and the formation of production relations among seaweed farmers in Punaga Village, South Sulawesi. A qualitative approach was employed using participant observation, in-depth interviews, and document analysis. The findings indicate that trust, communal norms, and local social networks are central to seaweed farming practices. Social capital functions as a mechanism for information exchange, access to production inputs, and collective labor arrangements. However, the research also reveals that strong social capital fosters patron client relationships that reinforce the dominance of punggawa/pappalele in controlling capital and distribution channels. Closed social networks produce exclusivity and limit economic mobility for new farmers. These findings suggest that social capital is ambivalent: while it supports social cohesion, it also reproduces structural inequality. Strengthening local institutions and developing more inclusive social capital are essential to promoting independence and equity in aquaculture production systems.